2012
DOI: 10.4103/0028-3886.93601
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-related disorders among a healthy population in South India

Abstract: SRDs are widely prevalent in India. Considering the health implications and poor awareness, there is a need to sensitize physicians and increase awareness among the public.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
102
4
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(112 citation statements)
references
References 20 publications
3
102
4
3
Order By: Relevance
“…Ninety patients with 'migraine without aura' (mean age: 31.76 ±8.2 years; M:F: 19:71) who were not on migraine prophylaxis were included for the study. Ninety age and gender matched healthy subjects without migraine (age: 31.76± 8.2 years ; M:F =19:71) were randomly selected from a large cohort of 1150 individuals who were evaluated in an epidemiological study at the same centre for detection of the prevalence of sleep abnormalities in the general population [5]. Institutional ethics committee approved the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ninety patients with 'migraine without aura' (mean age: 31.76 ±8.2 years; M:F: 19:71) who were not on migraine prophylaxis were included for the study. Ninety age and gender matched healthy subjects without migraine (age: 31.76± 8.2 years ; M:F =19:71) were randomly selected from a large cohort of 1150 individuals who were evaluated in an epidemiological study at the same centre for detection of the prevalence of sleep abnormalities in the general population [5]. Institutional ethics committee approved the study.…”
Section: Methodsmentioning
confidence: 99%
“…The ESS has a total of 8 situations for which the most appropriate response has to be decided by the respondent. A 'NIMHANS comprehensive sleep disorders questionnaire (NCSDQ)' was designed at our center (NIMHANS) to document sleep related symptoms [5]. Initially, a pilot study was undertaken on 50 individuals to assess the feasibility/ applicability of the questionnaire and also estimated problems in response.…”
Section: Evaluation Of Sleepmentioning
confidence: 99%
“…[5][6][7] In India, the prevalence of insomnia is found to vary between 14 to 18.7% in general population. [8][9][10] Earlier studies have indicated that there is an association between insomnia and hypertension incidence. [11][12][13] In a study in Chinese population, the prevalence of hypertension in those with no insomnia, occasional insomnia and frequent insomnia was reported to be 37.3%, 43.0% and 48.0% respectively.…”
Section: Introductionmentioning
confidence: 99%
“…There are several evidences to indicate that sleep deprivation disturbs cognition, working memory and attention [20][21][22][23][24][25][26][27][28][29]. However, studies on the effects of total sleep deprivation (SD) and on theta coherence among HPC, Amyg and PFC are not available.…”
mentioning
confidence: 99%